A technical method to improve NOx/NH3 mixing ratio in SCR system and its engineering applications. Issue 6 (December 2019) - Liu, Guofu; Cui, Yidong; Ji, Jiaqing; Shen, Dekui; Wang, Qi; Li, Chao; Luo, Kai Hong
Abstract: A technical method for diagnosing the distribution of NOx flux within the cross-section area in front of ammonia injection grid (AIG) was proposed for guiding the valve-tuning of AIG branch-pipes, in order to optimize the NOx /NH3 mixing ratio in the selective catalytic reduction (SCR) system of power plant. The weight coefficient of each branch-pipe in AIG system can be quantitatively determined with regard to the distribution of NOx flux in the corresponding sub-zone of the cross-section area. The control strategy of the valves for different AIG branch-pipes can be achieved for guiding the NH3 injection and improving the NOx /NH3 mixing ratio within the whole cross-section area in front of AIG. The technology has been applied on one side of the SCR system flue-gas tunnels (normally two tunnels for the SCR system called as A-side and B-side) of a 660 MW plant for more than one year. The ammonia consumption rate of the SCR system was reduced about 12.62% and the uniformity of outlet NOx distribution was estimated to be greatly improved by about 79.01% with regard to the standard deviation. The rising rate of the flue gas resistance of the air preheater was slown down by 39.18% compared to that of the other flue-gas tunnel of SCR system. This implied that the formation of the sticky ammonium bisulfate (ABS) on air preheater was significantly inhibited through the application of this technology. Graphical abstract: Image 1 Highlights: NH3 injection strategy of AIG area was obtained via analysis of NOx flux distribution. Ammonia consumption rate and smoke-flow resistance rising rate was limited. The uniformity of outlet NOx distribution was greatly improved.